MODEL DEVELOPMENT OF CLINICAL INFORMATION SYSTEM ADOPTION BY PHYSICIANS BASED TECHNOLOGY ACCEPTANCE MODEL BY CONSIDERING HUMAN, ORGANIZATION AND TECHNOLOGY FACTORS - ADITYA - NIM ; 23415012 , RIZKY
Nowadays, Information systems in Indonesia has grown rapidly in manufacturing and service industries. Hospitals as one of the providers of health services for the people are required to always provide the best service for patients. One way to improve the quality of health services in healthcare institution is to use clinical information systems (CIS), such as electronic medical records and clinical decision-making systems. In addition using information system can reduce paper use in hospitals industry, other countries prove that using information technology regularly and integratedly can improve access to health services in patients. However, the rate of CIS adoption in Indonesia especially by physicians is still relatively low due to various factors. Therefore, some research was conducted to determine the factors that influence the adoption of physicians to use CIS. In this research, the adoption of the use of CIS is described through usage behavior variable. This research integrates technology, organization and human context with Technology Acceptance Model as the main model. Previous studies tested that three context separately but in this research are the context involved in model development. Then this research brings the technostress factor that has not been used for the usage of CIS by physicians. This research used 296 physicians who have used SIK as a respondent. The data is used to test the relationship between the constructs. Structural equation modeling is used as a statistical method to test the relationship between the constructs. There are 20 hypotheses tested in this research consisting of 17 hypotheses on the structural model and three hypotheses on the measurement model. From the results of data processing shows that the technology dependence and self efficacy affect the technostress. On the other hand social influence, service quality and technostress affect the physicians intention in using CIS. Then the service quality and the information quality affect the perceived usefulness of using CIS, while the service quality and system quality affect the perceived ease of use of using CIS. Perceptions of perceived usefulness and perceived ease of use on the Technology Acceptance Model affect the intentions to use CIS and intention to use may affect CIS usage behavior. In addition, this research also shows that not all variables of technological, organizational and human aspects are tested has significant influence on perceived usefulness, perceived ease of use and intention to use CIS. The result also revealed that technostress in using CIS is a higher-order construct of overload, complexity and uncertainty of the technology used.